Analisis Putusan Pengadilan Agama Kota Kediri Nomor 0018/Pdt.P/2020/PA.Kdr tentang Dispensasi Kawin - Nuril Fahmi; Nur Hikmah; Moh. Usvi; Devi Nur; Eka Chandra; Sanuri Sanuri (Ma’mal: Jurnal Laboratorium Syariah dan Hukum, 2021)
Abstract: This study aims to analyze the Kediri Religious Court Number 0018/Pdt.P/2020/PA decision.Kdr. About Marriage Dispensation. Marriage dispensation has the meaning of an exception from the general rule for exceptional circumstances concerning the age of marriage, namely relief from restrictions. In the case of a marriage dispensation application filed at the Kediri Religious Court, the judge granted the Petitioner's request with a marriage dispensation to his 18-year-old daughter. The verdict is based on evidence and witnesses in court. Among the witness statements are that although the daughter is still 18 years old, she is already good at taking care of the housework, the husband-to-be who works as an entrepreneur earns Rp. 2,500,000 every month, the prospective bride and groom have been in love for two years, so the marriage is done to prevent forbidden things between them. In the perspective of Islamic law, the request is by the fiqh rule "Rejecting damage takes precedence over bringing benefit (which is not certain)." Keywords: Kediri City Religious Court, Prospective Bride, Marriage Dispensation. Abstrak: Penelitian ini bertujuan untuk menganalisis putusan Pengadilan Agama Kediri Nomor 0018/Pdt.P/2020/PA.Kdr. tentag Dispensasi Kawin. Dispensasi kawin mempunyai arti pengecualian dari aturan umum untuk keadaan yang khusus tentang usia perkawinan, yakni keringanan atas batasan. Pada perkara permohonan dispensasi kawin yang diajukan di Pengadilan Agama kediri ini, hakim mengabulkan permohonan Pemohon dengan dispensasi kawin kepada putrinya yang berusia 18 tahun. Putusan tersebut didasarkan pada bukti dan saksi di pengadilan. Di antara keterangan saksi adalah meski sang anak perempuan masih berusia 18 namun ia sudah pandai mengurus pekerjaan rumah, calon suami yang bekerja sebagai wiraswasta berpenghasilan Rp. 2.500.000 setiap bulan, calon mempelai telah menjalin asmara selama 2 tahun sehingga perkawinan dilakukan untuk mencegah terjadinya hal-hal yang terlarang di antara keduanya. Dalam perspetif hukum Islam, permohonan tersebut sesuai dengan kaidah fikih “Menolak kerusakan lebih didahulukan daripada mendatangkan kemaslahatan (yang belum pasti)”. Kata Kunci: Pengadilan Agama Kota Kediri, Calon Mempelai, Dispensasi Kawin.